Corn processing in feedlot diets for Nellore cattle: intake, digestion sites and different techniques to estimate digestibility; and nutritional requirements and body composition of Nellore heifers by dual-energy X-ray absorptiometry or by carcass sections - Godoi, Letícia Artuzo (2021)
This thesis was developed based on four studies. In the first manuscript the objective were to (1) verify the influence of flint corn ensiling methods on intake; rumen digestion kinetics; microbial efficiency; rumen pH; and ruminal, intestinal, and total tract digestibilities in Nellore bulls; and (2) determine whether snaplage (SNAP) plus a mineral–protein supplement could be used successfully to supply energy, fiber, and protein in a finishing diet without causing ruminal acidosis. Five rumen-cannulated Nellore bulls (265 ± 18.2 kg, 8 ± 1.0 mo old) were distributed in a 5 × 5 Latin square design. Five different diets were evaluated. Three experimental diets [dry matter (DM) basis] comprised 600 g/kg dry ground corn grain (DCG), high–moisture corn (HMC), or reconstituted corn grain silage (RCG) plus 300 g/kg whole-plant corn silage and 100 g/kg mineral–protein supplement. SNAP was included in two experimental diets, namely 900 g/kg SNAP (SNAP-90) or 800 g/kg SNAP + 100 g/kg stalklage (SNAP-80) plus 100 g/kg mineral–protein supplement. The experiment lasted 115 d, with five periods of 23 d. These periods were divided into two subperiods of 14 d for dietary adaptation and 9 d for ruminal emptying, omasal, urinary, and fecal sample collection. Statistical analyses were performed using the MIXED procedure in SAS 9.4. DCG-based diet tended (P = 0.07) to increase DM and organic matter (OM) intake. Diets based on HMC, RCG, SNAP-80, and SNAP-90 increased (P < 0.05) intestinal and total digestion of DM, OM, and starch compared with the diet based on DCG. There was greater (P < 0.05) microbial crude protein synthesized per kg of crude protein for bulls fed HMC-based diet compared with bulls fed DCG-, SNAP-80-, or SNAP-90-based diets. Intake and passage rates of starch were lower (P < 0.05) and digestion rate of starch tended to be lower (P = 0.06) for DCG-based diet compared with the other diets. The rumen pH was affected (P < 0.05) by diets. However, rumen pH was above 6.2 for all evaluated diets. Also, there was no effect of flint corn processing methods on ruminal, intestinal, and total tract digestibility of fiber. In conclusion, diets based on HMC, RCG, SNAP-80, and SNAP-90 can be used to improve starch availability without negatively affecting ruminal parameters. HMC and RCG are viable processing methods for flint corn and can replace DCG to improve nutrient digestibilities. In addition, SNAP could be used as an exclusive fiber and energy source forfeedlot-finished Nellore bulls. The objectives of the second manuscript were to 1) evaluate the effects of flint maize processing methods on the estimation of the readily soluble fraction (a), the potentially degradable fraction (b), and the rate of degradation of b (c) for dry matter (DM), organic matter (OM), and starch in the rumen; and 2) verify whether two different applications of in situ technique can be used to estimate in vivo DM, OM, and starch digestibilities. Animals and diets used in the second manuscript were the same as in the first manuscript. Digestibilities were estimated using in vivo procedure (first manuscript) or predicted from in situ technique using a single 24 h incubation point, or an equation proposed in previous literature. Diets based on ensiled grains presented greater (P < 0.05) fraction a and c and lower (P < 0.05) fraction b of DM, OM, and starch compared to DCG. Both alternative use of in situ technique accurately estimated (P > 0.05) in vivo DM, OM, and starch digestibilities. The results suggest that ensilage process may increase availability of nutrients. The two different applications of in situ technique showed precision and accuracy to estimate in vivo digestibility. The third study aimed to (1) verify the effects of dietary crude protein (CP) levels of early-weaned calves; and (2) the influence of flint maize processing methods on intake, total tract nutrient digestibilities, and performance of Nellore heifers. Nineteen early-weaned Nellore calves (4 ± 0.5 mo; 108 ± 21.0 kg) were used. In phase 1, animals were fed one of the following diets for 112 d: 130, 145, or 160 g CP/kg dry matter (DM). In phase 2, animals received one of two diets during 84 d: 0.60 dry ground maize grain, 0.30 whole-plant maize silage plus 0.10 mineral and protein supplement, or 0.90 snaplage plus 0.10 mineral and protein supplement. In phase 1, intake and digestibility of DM, organic matter, neutral detergent fiber, and starch were not affected (P > 0.05) by increasing dietary CP levels. Daily total urinary N and urinary urea N increased (P < 0.05) in response to increasing dietary CP levels. Animal performance was not affected (P > 0.05) by dietary CP content. In phase 2, maize processing methods did not affect (P > 0.05) intake and digestibility of dietary components as well as animal performance, carcass characteristics, and carcass composition. Therefore, we conclude that dietary CP concentrations of 130 g/kg DM can be indicated for early-weaned Nellore calves. However, more studies are recommended to validate this result and to evaluate levels below 130 g CP/kg DM for early- weaned Nellore calves. Moreover, snaplage could be used as an exclusive fiber and energy source for cattle finished in feedlot. The fourth manuscript was developed to (1) estimate energy and protein requirements of Nellore female; (2) test the prediction equations of carcass chemical and physical composition and empty body chemical composition proposed by BR-Corte system; (3) verify whether chemical and carcass physical composition and empty body chemical composition could be successfully estimated from the composition of carcasssections; and (4) evaluate a method to predict the carcass and empty body composition through empirical equations using dual energy X-ray absorptiometry (DXA). Nineteen early-weaning Nellore female calves (initial age of 4 ± 0.5 mo; initial BW of 108 ± 21.0 kg) born from primiparous cows were used. Four calves were used as baseline reference animals and were slaughtered at the beginning of the experiment. The experiment consisted of two phases. In phase 1 animals were randomly assigned (n = 5/treatment) into 3 performance groups. In phase 2 animals were randomly divided into 2 groups: maintenance (n = 3) and performance (n = 12, being n = 6/treatment). At the end of phase 2, animals were slaughtered, and non-carcass components were sampled. The left half-carcass of each animal was divided into seven sections which were scanned using DXA, totally dissected into muscle, fat, and bone, and sampled. Nonlinear regression equations were developed to predict heat production from metabolizable energy (ME) intake and retained energy (RE). The net energy (NE) requirements for maintenance and ME for maintenance were 72.5 and 103.4324 kcal/EBW0.75/d, respectively. The efficiency of ME utilization for maintenance was 70%. The equation obtained for NE for gain (NEg) was: NEg (Mcal/ EBW0.75/d) = 0.0726 × EBW0.75 × EBG0.6845, where EBG is the empty body gain, and the efficiency of ME utilization for gain was 44.46%. Net protein requirement for gain (NPg) was: NPg (g/d) = 241 × EBG – 18,0939 × RE. The composition of carcass sections and DXA measurements of carcass sections can be used to estimate the composition of the whole carcass and empty body. However, more studies are necessary to validate this result. Equations proposed by BR-CORTE system are recommended for estimating carcass and empty body chemical composition and carcass physical composition of Nellore heifers. Keywords: Beef cattle. Corn processing methods. Nutritional requirements. Body composition.